Analysis Of The Effect Of Service Quality Dimensions On Patient Satisfaction With Empathy As A Dominant Factor At Al-Irsyad Hospital Surabaya In 2025 - Suwardi; Pipit Festi; Mochamad Mockhlas (LP2IHKI UMSurabaya, 2026)
Abstract Background : Patient satisfaction is one of the important indicators in evaluating hospital service quality. Service quality dimensions such as tangible, reliability, responsiveness, assurance, and empathy are considered factors that may influence patient satisfaction. Aim s : This study aims to analyze patient satisfaction with services at Al-Irsyad Hospital Surabaya in 2025. Methods : This study used a cross-sectional design with a population of 4,875 patients and a sample of 110 respondents selected through purposive sampling. The research was conducted in July 2025. Data were collected using a questionnaire based on service quality dimensions, namely tangible, reliability, responsiveness, assurance, and empathy. Statistical analysis was performed using the Chi-Square test and multivariate logistic regression analysis. Results : The Chi-Square test results showed significant relationships between reliability (p=0.021), assurance (p=0.015), and empathy (p=0.008) variables with patient satisfaction (p<0.05). Meanwhile, tangible and responsiveness variables did not show significant relationships with patient satisfaction. Multivariate logistic regression analysis identified empathy as the most dominant factor affecting patient satisfaction (p=0.003; OR=9.472). Conclusion : Improving hospital service quality should focus on strengthening interpersonal communication, increasing individual attention to patients, and improving the competence and professional attitude of health workers to provide patient-centered services. Keywords : Patient satisfaction, service quality, SERVQUAL, hospital. Abstrak Latar Belakang : Kepuasan pasien merupakan salah satu indikator penting dalam menilai kualitas pelayanan rumah sakit. Kualitas pelayanan yang mencakup dimensi tangible, reliability, responsiveness, assurance, dan empathy dapat memengaruhi tingkat kepuasan pasien terhadap pelayanan kesehatan yang diberikan. Tujuan : Penelitian ini bertujuan untuk menganalisis kepuasan pasien terhadap pelayanan di Rumah Sakit Al-Irsyad Surabaya Tahun 2025. Metode : Desain penelitian yang digunakan adalah cross sectional dengan jumlah populasi sebanyak 4.875 pasien dan sampel penelitian sebanyak 110 responden yang dipilih menggunakan teknik purposive sampling. Penelitian dilaksanakan pada bulan Juli 20252. Pengumpulan data dilakukan menggunakan kuesioner berdasarkan dimensi kualitas pelayanan (tangible, reliability, responsiveness, assurance, dan empathy). Analisis data dilakukan menggunakan uji Chi-Square dan uji regresi logistik multivariat. Hasil : Hasil analisis statistik menggunakan uji Chi-Square menunjukkan adanya hubungan yang bermakna antara variabel reliability (p=0,021), assurance (p=0,015), dan empathy (p=0,008) dengan kepuasan pasien (p<0,05). Sementara itu, variabel tangible dan responsiveness tidak menunjukkan hubungan yang signifikan. Hasil uji regresi logistik multivariat menunjukkan bahwa faktor yang paling dominan memengaruhi kepuasan pasien adalah empathy (p=0,003; OR=9,472). Kesimpulan : Pihak rumah sakit perlu meningkatkan mutu pelayanan melalui penguatan komunikasi interpersonal, peningkatan perhatian individual kepada pasien, serta peningkatan kompetensi dan sikap profesional tenaga kesehatan dalam memberikan pelayanan yang berorientasi pada kebutuhan pasien. Kata Kunci : Kepuasan pasien, kualitas pelayanan, SERVQUAL, rumah sakit.